1997
DOI: 10.1074/jbc.272.2.1095
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transducin by a Xenopus Short Wavelength Visual Pigment

Abstract: Phototransduction in cones differs significantly from that in rods in sensitivity, kinetics, and recovery following exposure to light. The contribution that the visual pigment makes in determining the cone response was investigated biochemically by expressing a Xenopus violet cone opsin (VCOP) cDNA in COS1 cells and assaying the light-dependent activation of transducin. Light-exposed VCOP stimulated [35 S]guanosine 5-(␥-thio)triphosphate nucleotide exchange on bovine rod transducin in a time-dependent manner w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 29 publications
6
59
0
Order By: Relevance
“…For example, cone visual pigment was purified and its quantum efficiency was shown to be similar to that of the rod pigment rhodopsin (11). In other studies, with the use of a purified cone protein, its interaction with a rod protein was measured (12)(13)(14)(15)(16). To know the mechanism characterizing the cone photoresponses, however, it is essential to measure the interaction between cone proteins and compare the result with the corresponding reactions in rods.…”
mentioning
confidence: 99%
“…For example, cone visual pigment was purified and its quantum efficiency was shown to be similar to that of the rod pigment rhodopsin (11). In other studies, with the use of a purified cone protein, its interaction with a rod protein was measured (12)(13)(14)(15)(16). To know the mechanism characterizing the cone photoresponses, however, it is essential to measure the interaction between cone proteins and compare the result with the corresponding reactions in rods.…”
mentioning
confidence: 99%
“…What Determines the Number of Transducin Molecules Activated by P-opsin?-We have shown that P-opsin activates rod transducin in a light-dependent manner that is similar to rhodopsin but distinct from violet cone opsin (27). Moreover, Popsin has a meta-stable active conformation that is very similar to metarhodopsin II.…”
Section: Discussionmentioning
confidence: 97%
“…2) at 4°C. Membranes and 11-cis-retinal (final concentration, 5 M) were incubated overnight, solubilized by the addition of 10% (w/v) dodecyl maltoside (DM) to a final concentration of 1% DM, and incubated for 2 h. Insoluble material was removed by centrifugation at 40,000 ϫ g for 1 h. The P-opsin protein was purified on 1D4-Sepharose by immunoaffinity chromatography (26,27). Rhodopsin from bovine retina was purified in parallel with P-opsin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations